A Review Paper on Energy Efficient Routing in Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2014)
The wireless sensor networks have been studied extensively in the recent years. Such networks are made of several thousand of sensors propagated in a geographical area. There are many different applications for such networks including military, environment monitoring, disaster, ﬁre ﬁghting and protection, and home applications. Sensors are very simple identical electronic devices equipped with a processor and small storage memory and a communication channel. The sensors can communicate to each other through wireless links, and most of the times we use radio frequency channels for the purpose of communication. The routing problem in the sensor networks has been studied by many researchers. Sequential Assignment Routing (SAR) is proposed in [5], and it takes into account the energy constraints by making a tree rooted in the central node. The tree starts to -grow toward the sensors on the paths with enough residual energy.